Features of the Declared and Real Attitude of Youth Towards Representatives of Other Countries - Levus, N.; Ilchyshyn, N. (Psychological Prospects Journal, 2013)
In the article a theoretical ground and empiric study of differences are carried out between the declared and real attitude of young people toward the representatives of other countries. For most investigated (76 %) characteristic is adequate attitude toward other ethnic groups. Significant discrepancy is declared and real attitude found in those subjects who are dependent on the opinions of others, and in problem situations followed a strategy to avoid. Factor of social distance from other ethnic groups do not act as personal preferences of young people, as political, social and economic conditions.